Find the integral

(sinx+cosx)4(cosxsinx)4dx=? \large \int \dfrac{ (\sin x + \cos x)^4}{(\cos x - \sin x)^4} \, dx = \, ?

#Calculus

Note by Alaa Yousof
5 years, 3 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

For simplicity sake, let ss and cc denote the functions sinx,cosx\sin x , \cos x respectively, then we have s2+c2=1,2cs=sin(2x)s^2 + c^2 = 1 , 2cs = \sin(2x) .

Then, (s+c)4=s4+c4+4cs(s2+c2)+6(cs)2=(s2+c2)22(cs)2+4cs+6(cs)2=1+4cs+4(cs)2(sc)4=s4+c44cs(s2+c2)+6(cs)2=(s2+c2)22(cs)24cs+6(cs)2=14cs+4(cs)2 \begin{aligned} (s+c)^4 &=& s^4 + c^4 + 4cs(s^2 + c^2) + 6(cs)^2 = (s^2 + c^2)^2- 2(cs)^2 + 4cs + 6(cs)^2 = 1 + 4cs + 4(cs)^2 \\ (s-c)^4 &= & s^4 + c^4 - 4cs(s^2 + c^2) + 6(cs)^2 = (s^2 + c^2)^2- 2(cs)^2 - 4cs + 6(cs)^2 = 1 - 4cs + 4(cs)^2\end{aligned}

Taking their ratio gives: 1+4cs+4(cs)214cs+4(cs)2=1+8sc14cs+4(cs)2=1+4sin(2x)12sin(2x)+sin2(2x)=1+4sin(2x)(sin(2x)1)2=1+4[1sin(2x)1+1(sin(2x)1)2] \begin{aligned} \dfrac{1 + 4cs + 4(cs)^2}{1 - 4cs + 4(cs)^2 } &=& 1 + \dfrac{8sc}{1 - 4cs + 4(cs)^2} \\ &=&1 + \dfrac{4\sin(2x)}{1 - 2\sin(2x) + \sin^2(2x)} = 1 + 4 \cdot \dfrac{\sin (2x)}{(\sin(2x) - 1)^2} \\ &=& 1 + 4 \left [\dfrac1{\sin(2x) - 1}+ \dfrac1{(\sin(2x) - 1)^2} \right ] \end{aligned}

So we're integrating the final expression in the equation above. Use half angle tangent substitution, we have t=tan(x)dx=dt1+t2,sin(2x)=2t1+t2 t = \tan(x) \Rightarrow dx = \dfrac{dt}{1+t^2} , \sin(2x) = \dfrac{2t}{1+t^2} . Use partial fractions to finish it off, note that 2t1t2=(t1)22t - 1 - t^2 = -(t-1)^2 .

Can you finish it off from here?

Pi Han Goh - 5 years, 3 months ago

Log in to reply

no what are the next steps please

who ting - 5 years, 2 months ago

Log in to reply

What do you mean?

Pi Han Goh - 5 years, 2 months ago

Log in to reply

@Pi Han Goh how will we use the partial fractions

who ting - 5 years, 2 months ago

Log in to reply

@Who Ting I don't know where exactly you're stuck on. Please show your steps.

Pi Han Goh - 5 years, 2 months ago
×

Problem Loading...

Note Loading...

Set Loading...